Inovasi Pangan Fermentasi Tempe Gembus dengan Penambahan Jantung Pisang sebagai Sumber Probiotik untuk Meningkatkan Kesehatan Pencernaan pada Lansia - Dwi Nurul Qomariah; Dea Amanda Caressa; Elita Endah Mawarni (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Health issues among the elderly are often related to declining bodily functions, digestive disorders, and specific nutritional needs for easily digestible foods. The 60-and-older age group is at high risk for gastrointestinal disorders due to low fiber intake. Therefore, alternative foods are needed that are soft in texture, neutral in taste, safe, and nutritious. One potential solution is the development of food products based on tempeh gembus with the addition of banana hearts, which are rich in fiber, soft in texture, and readily available. This study employed an experimental method using a Completely Randomized Design (CRD) to test three formulation variations (F1, F2, F3). The nutritional content of formulation F1 includes energy 111.575 kcal, carbohydrates 20.185 g, protein 6.91 g, fat 0.355 g, and fiber 6.67 g. Formula F2 contains 88.225 kcal of energy, 14.095 g of carbohydrates, 7.72 g of protein, 0.205 g of fat, 7.3 g of fiber, and 0.0015% flavonoids. Formula F3 has 107.015 kcal of energy, 7.995 g of protein, 0.295 g of fat, 6.88 g of fiber, and 0.0021% flavonoids. In conclusion, the best tempeh with added banana hearts is Formula F2, with its nutritional content, fiber, flavonoids, and BAL >10⁸ CFU/g, which has the potential to serve as a functional food and probiotic source to help improve digestive health in the elderly. Further testing is recommended directly on elderly groups, along with product shelf-life testing.